SIDA PENAMBANGENSIS (MALVACEAE), A NEW SIDA SPECIES FROM EAST JAVA, INDONESIA - THEMAS FELAYATI; HIMMAH RUSTIAMI; RATNA SUSANDARINI (BRIN Publishing (Penerbit BRIN), 2024)
A new species of Sida from Penambangan Village, Sidoarjo, East Java related to Sida acuta is described as Sida penambangensis Felayati, Rustiami & Susandarini. It is distinguished from Sida acuta Burm.f. with at least six characters such as stem covered with obvious long trichomes, reddish-purple at upper leaf margin, stipule subulate-falcate, pedicels not articulated, mericarps 9–11 with pair linear awns 0.8 mm long with simple and stellate pubescence. It is described and illustrated here as a species new to science.